Innovative didactic designs: visual analytics and visual literacy in school. Issue 3 (2nd October 2017) - Stenliden, Linnéa; Nissen, Jörgen; Bodén, Ulrika
Abstract: In a world of massively mediated information and communication, students must learn to handle rapidly growing information volumes inside and outside school. Pedagogy attuned to processing this growing production and communication of information is needed. However, ordinary educational models often fail to support students, trialing neither efficient tools such as visual analytics (VA) nor educational improvements via, for example, knowledge visualization (KV). This paper accordingly explores the facilitation and realization of teachers' development of innovative didactic designs, that is, thoroughly conceived lesson plans in which VA and KV are combined in learning activities in school settings. The aim is to clarify vital components emerging in innovative didactic designs intended to support students' visual literacy, knowledge construction and visualize knowledge. These components are central to better understanding future outcomes in classrooms where visual learning tools are applied. This design-based research emerged from a 'teacher researcher team' comprising 15 teachers and four researchers, VA, theory, etc. Actor network theory, applied in analyzing significant issues and developments, revealed that teachers were aware not only to concentrate learning how to use VA but also considering how students can demonstrate growing knowledge – a more challenging tasks than simply introducing VA for students and teachers.